THE SOCIAL AND SPIRITUAL DEVELOPMENT OF STAGE SPEECH AND THE FACTORS CONTRIBUTING TO ITS FORMATION AS A SCIENCE (Multidisciplinary Journal of Science and Technology, 2025)
In this article, the social and spiritual development of stage speech – the primary medium of theatrical art – and the factors contributing to its formation as a science are examined. Furthermore, significant research on stage speech is analyzed, the importance of stage speech in social life and personal development is elucidated, and the evolution of its methodology is investigated.